Exploring the determinants of family planning practices among women with diabetes and no pregnancy intention in Malaysia: women’s voices - Ismail, Irmi Zarina; Ng, Chirk Jenn; Lee, Ping Yein; Hussein, Norita (Korean Journal of Family Medicine, 2026)
Background: Contraception is essential for women with diabetes to reduce adverse pregnancy outcomes. However, the contraception rate among this high-risk group remains low. This study explored the determinants of contraceptive practices among multi-ethnic Asian women with diabetes. Methods: This exploratory qualitative study on the preconception care of multi-ethnic, reproductive-age women with diabetes was conducted at four public health clinics in Negeri Sembilan, Malaysia. Semi-structured, in-depth interviews were conducted, audio-recorded, and transcribed. An interpretive thematic analysis was performed on data regarding contraception among 19 women who expressed no desire for pregnancy. Results: Health concerns, perceived susceptibility to pregnancy, lack of knowledge regarding contraception and conception, and prevailing pregnancy norms influenced contraceptive practices. Many factors affecting pregnancy planning were unrelated to diabetes, such as perceived pregnancy susceptibility, religious orientation, societal norms, husband's preferences, and inadequate contraception knowledge. Conclusion: Family planning and reproductive health must be included in routine clinical consultations for women with diabetes. While this study re-emphasizes the influence of diabetes on women's decisions to use contraception, their choices are also shaped by personal and social factors. Healthcare providers must adopt a more open approach toward women's perspectives on pregnancy planning and further explore their values and underlying issues to promote effective contraception, considering the benefits.